Lack of pediatric surgical cardiac care in Pakistan - Muhammad Abdul Rehman; Anooja Rani; Maheen Fatima Hussaini (Journal of the Pakistan Medical Association, 2021)
Dear editor, Over the past several years the highest incidence rates of congenital heart diseases (CHD) have been reported from African and Asian countries with unprecedented surge in countries like North Korea and Pakistan [1]. Pakistan has seen a subtle but continuous increase in the percentage of CHD-related deaths in the pediatric age group (0-14 years) over the last few years. From 2017 to 2019, 2.07% (10,701.31), 2.13% (10,408.06) and 2.19% (10,403.35) of children died due to CHDs respectively [2]. Hence, the pediatric surgical cardiac care currently available cannot cater to the needs of an enormously populated Pakistan. A nationwide survey carried out in 2014 highlighted the insufficiency in the number of functional pediatric cardiac care units in Pakistan where out of 16 operational pediatric intensive care units (PICUs) merely three were dedicated cardiac PICUs. The report also elicited that only 155 beds were present in the aforementioned 16 PICUs [3]. Despite having around 60,000 babies born with CHD annually, as recorded in a 2017 report, Pakistan only has 4 hospitals that perform pediatric cardiac surgery [4]. Besides, the study reports that over 60 per cent of children with CHD fail to live through the first few years of their lives, elucidating the dire need for more pediatric cardiac surgery centers and PICUs. In order to decrease pediatric CHD mortality, it is vital to highlight and address the need for accessible and modern infrastructure, to diagnose efficiently, treat and follow-up with appropriate post-operative care. Inclusion of a vigorous neonatal screening system, such as through pulse oximetery, may also help identify CHD in neonates with a promising certainty; to plan the delivery of surgical care at an appropriate age [5,6]. Pediatric physicians, alongside government support, must raise awareness regarding risk factors for CHDs, such as maternal diabetes increasing the risk of transposition of the great vessels. Furthermore, a new nationwide survey should be conducted to consider all rural and metropolitan pediatric cardiac patients, their access to healthcare facilities, and mortality. All to supplement and better understand the dire need for sufficient pediatric cardiological healthcare. Continuous...